2012
DOI: 10.1021/es301685g
|View full text |Cite
|
Sign up to set email alerts
|

Visual Color Perception in Green Exercise: Positive Effects on Mood and Perceived Exertion

Abstract: Positive effects of green exercise on physical and psychological wellbeing have been found, yet little is known about the underlying cognitive mechanisms responsible for such effects. The purpose of this visual sensation study was to establish the extent to which the color green, as a primitive visual feature of many natural environments, contributes to the green exercise effect. Fourteen participants performed three moderate-intensity 5-min cycling tasks (50% peak power output) while watching video footage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
125
9
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(154 citation statements)
references
References 31 publications
12
125
9
2
Order By: Relevance
“…The associations of the color green with calmness, growth and naturalness seem to represent fairness with respect to the contextual factors of combat sports , 2014. Thus, we perceive that green should oppose something unnatural, false or fake (Akers et al, 2012;Fehrman & Fehrman, 2004;Gil & Le Bigot, 2014;Lichtenfeld et al, 2012;Mazar & Zhong, 2010). Because of this association with fairness, athletes wearing green in combat sports could benefit from milder and more positive refereeing decisions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The associations of the color green with calmness, growth and naturalness seem to represent fairness with respect to the contextual factors of combat sports , 2014. Thus, we perceive that green should oppose something unnatural, false or fake (Akers et al, 2012;Fehrman & Fehrman, 2004;Gil & Le Bigot, 2014;Lichtenfeld et al, 2012;Mazar & Zhong, 2010). Because of this association with fairness, athletes wearing green in combat sports could benefit from milder and more positive refereeing decisions.…”
Section: Discussionmentioning
confidence: 96%
“…Most notably, Greenlees et al (2013) showed that soccer players facing a goalkeeper wearing a red uniform scored on fewer penalty kicks in soccer than those facing a goalkeeper wearing green. However, outside of sport, research emphasized a posi tive valence of green standing for calmness, pleasantness and growth (Akers et al, 2012;Clarke & Costall, 2008;Fehrman & Fehrman, 2004;Gil & Le Bigot, 2014;Lichtenfeld et al, 2012;Moller, Elliot, & Maier, 2009). Green is often used to present products and objects as healthy and natural, in contrast to some thing being unnatural, fake or false (cf.…”
mentioning
confidence: 99%
“…Based on previous studies on adults, it is possible that greenness and the positive effects of nature could also play a key role in activating young men. There is some evidence that exercising outdoors requires less exertion than exercising indoors [47,48]. Thus, young men with stronger nature relatedness might prefer to exercise outdoors.…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining participant ratings for preferred exercise environment and the aesthetic qualities of the location would help understand the degree of importance of specific components of the setting for changing affective states. The cognitive mechanisms that explain mental health benefits derived from green exercise are not yet well understood (Akers et al, 2012), hence it is possible that the outdoor natural setting in this study did not adequately reflect the underlying effective elements of green exercise.…”
Section: Discussionmentioning
confidence: 99%